UMM AL-BARAHIN AND ITS RELATION WITH MALAY JAWI BOOKS - Abdul Rahim, Mohd. Hisyam; Rusdi, Mikdar; al-Edrus, Syed Muhammad Dawilah (Journal of Techno-Social, 2012)
Umm al-Barahin is a theology masterpiece that delivers a big impact on Malay Jawi Books writing. The book has been fundamental in learning and discussing the attributes of Allah in Malay world. This article found that there are many works of adaption and translation based on Umm al-Barahin produced by Malay traditional scholars. The sustainability of teaching based on this books until now are really amazing. Malay Jawi Books are also a sign of the Islamic scientific tradition that developed in Malay world. The process are rooted on translation and adaptation activities from the Arabic masterpiece to Malay language in Jawi writing.